Tinjauan Terhadap Modus-Modus Kejahatan Dalam Hukum Cyber Crime - Musa Sahat Tobing; Utari Wulandari; Marito Sari Sihotang; Raihana Raihana (Jurnal Hukum dan Sosial Politik, 2023)
When surfing the digital world, you need to be careful about feeling comfortable on social media. Cybercrime is a form of crime that arises because of the use of internet technology. In line with advances in information technology, several crimes have emerged which are often interpreted as crimes committed in cyber space or areas. Rusbagio Ishak, Kadit Serse Polda Central Java said, this cyber crime has the potential to cause losses in several fields: political, economic, socio-cultural. Cyber ​​crime is various kinds of illegal access to a data transmission. In other words, cybercrime is an illegal activity on a computer system or is included in the category of crimes in cyberspace. The target of this cyber crime is a computer connected to the internet network. Cyber ​​crime is carried out with various purposes. Starting from fun testing hacking skills, to serious crimes that can harm the victim financially. One of the cyber crimes that is rife in Indonesia is a social engineering attack or social engineering. Social engineering is a manipulation technique that exploits human error to gain access to personal information or valuable data.